Microstructural evolution and mechanical behaviour of high strength steel treated by quenching and partitioning process. (2017) - Mandal, G.; Ghosh, S.K.
Abstract: The present steel has been processed through thermo-mechanical controlled processing (TMCP) with the finish rolling temperature (FRT) of 850°C followed by air cooling (AC). Subsequently, the steel was subjected to partial (800°C) and full austenitisation (930°C) followed by quenching and partitioning (Q&P) process at 345°C below MS (365°C) temperature. The steel in as-rolled condition reveals mixed microstructures comprising ferrite and bainite with yield strength of 560 MPa and tensile strength of 1063 MPa along with an average total elongation of 15%. The attractive combination of tensile strength (933-1000 MPa) and ductility (26-29% total elongation) are attributed to the multiphase microstructure comprising ferrite, lath martensite and thin film like carbon enriched retained austenite after one step Q&P process.